Platelet hemostasis and endothelial status in postmenopausal women with some risk factors for coronary heart disease – the impact of hormonal therapy and anti-thrombotic prophylaxis - Stachowiak, Grzegorz; Niewiarowska, Jolanta; Wiktorska, Magdalena; Papiewska-Pająk, Izabela; Sacewicz, Izabela; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of study: the influence of transdermal hormone therapy (tHT) and anti-thrombotic prophylaxis (low doses of acetylsalicylic acid – ASA) on platelet hemostasis and endothelial function of menopausal women with risk factors for coronary heart disease (CHD). Material and methods: Study group were menopausal women (with 2 or more CHD risk factors) in which tHT composed of 17β-estradiol and NETA (G1, n=22) or the above tHT combined with low ASA doses were administered (ASA) (n=23). Controls were 16 premenopausal women. The following parameters were measured in blood: GP IIb/IIIa, E-selectin, endothelin-1 (ET-1), u-PAR. Duration of the therapy was 3 months. Results: Three-month treatment, both as tHT in G1, as well as tHT+ASA in G2, had no significant influence on the levels of GP IIb/IIIa, E-selectin, ET-1 and u-PAR. At the beginning of the study (T0), both groups of postmenopausal women were characterized, as compared to the premenopausal controls, by the higher levels of platelet receptor – GP IIb/IIIa. Conclusions: 1. Three-month tHT applied in the group of menopausal women with CHD risk factors did not influence endothelial function and platelet hemostasis. 2. The use of low ASA doses, as the anti-thrombotic prophylaxis of tHT in postmenopausal women with CHD risk factors, is not indicated. 3. Disadvantageous alterations in platelet hemostasis are observed after menopause.